The Effects of IFRS Adoption and Big 4 Audit Firms On Audit and Non-Audit Fees: Evidence from Ghana - Alhassan Musah; Fred Kwasi Anokye; Erasmus Dodzi Gakpetor (Journal of Accounting and Management Information Systems (JAMIS), 2018)
The study was conducted to examine the effect of IFRS adoption on audit and non-audit fee and also the relationship between the big4 audit firm and audit and non-audit fees. Using a sample of financial and non-financial firms in Ghana, the results show that IFRS adoption has a positive and significant relationship with audit and non-audit fees post IFRS adoption. The results further revealed that there is positive association between the year of IFRS adoption (transition period) and audit and non-audit fees. On the big4 audit firms, the results show that the big4 charge higher audit and non-audit fees than non-big4 as there was a positive and significant relationship between Big4 and audit and non-audit fees. The results support the argument that the adoption of IFRS increased the complexities of financial reporting and audit risk resulting in a higher audit and non-audit fees charged during the transition period and post IFRS adoption. The paper extends previous studies on the subject matter by including the year of IFRS adoption and non-audit fees within the context of a developing economy with weak financial regulatory regime.
Keywords: M41; M42; 650; International Financial Reporting Standards; Audit fees; Non-audit fees; Big4; Ghana National Accounting Standards